Expectations Formation and Forecasting of Vehicle Demand: An Empirical Study of the Vehicle Quota Auctions in Singapore - CHU, Sing-Fat (Institutional Knowledge at Singapore Management University, 2004)
This paper studies the expectations formation and forecasting of vehicle demand in Singapore under the vehicle quota system. Under the system, a car buyer must first bid for a vehicle license in monthly auctions in order to purchase a new car. We construct an econometric model to test the hypothesis that past bid distributions of the license auctions contain information that car buyers can use to update their expectations about the intensity of market demand, forecast the license premiums and formulate their bidding strategies in future auctions. Our empirical analysis indicates that past bid distributions have a good degree of predictive power for the license premiums.